2011
DOI: 10.1159/000324580
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of a Randomized Controlled Trial of Oral Appliance Therapy in Obstructive Sleep Apnea

Abstract: Background: Long-term trials are needed to capture information regarding the persistence of efficacy and loss to follow-up of both mandibular advancement device (MAD) therapy and continuous positive airway pressure (CPAP) therapy. Objectives: The aim of the study was to compare these treatment aspects between MAD and nasal CPAP (nCPAP) in a 1-year follow-up. Methods:Forty-three mild/moderate obstructive sleep apnea patients (52.2 ± 9.6 years) with a mean apnea-hypopnea index (AHI) of 20.8 ± 9.9 events/h were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(126 citation statements)
references
References 58 publications
5
115
1
5
Order By: Relevance
“…In 93 potentially relevant references, 17 papers were taken for a comprehensive evaluation. After retrieving the full articles, one was excluded because of duplicated data 18 and 2 were excluded because of nonclinical outcomes. 19,20 Finally, 14 studies were included in this metaanalysis.…”
Section: Withdrawals and Dropoutsmentioning
confidence: 99%
“…In 93 potentially relevant references, 17 papers were taken for a comprehensive evaluation. After retrieving the full articles, one was excluded because of duplicated data 18 and 2 were excluded because of nonclinical outcomes. 19,20 Finally, 14 studies were included in this metaanalysis.…”
Section: Withdrawals and Dropoutsmentioning
confidence: 99%
“…Three studies reported longer-term results from MAD treatment after 1-4 yrs, compared with CPAP [12], surgery [37] or between two types of MAD [21]. The majority (74%) of the RCTs used polysomnography (PSG), while the other researchers utilised limited sleep recordings or combinations of these methods to analyse sleep-disordered breathing.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…In randomized controlled trials comparing both modalities of treatment, CPAP therapy is consistently more effective in reducing sleep disordered breathing events. [6][7][8][9] While CPAP and MAS have similar subjective and cardiovascular outcomes, patients tolerate MAS better. [8][9][10][11] The superior patient satisfaction associated with the use of MAS reflects the relative simplicity and convenience of this form of treatment.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…[6][7][8][9]19 Randomized control trials have shown no significant differences in subjective sleepiness and quality of life when comparing CPAP to MAS. 8,20,21 Our study showed an interesting and important finding in terms of daytime sleepiness.…”
mentioning
confidence: 99%